Rapid loss of vaccine-acquired hepatitis B surface antibody after three doses of hepatitis B vaccination in HIV-infected persons. (March 2014) - Mizusawa, Masako; Perlman, David C; Lucido, David; Salomon, Nadim
HIV-infected individuals have poor responses to hepatitis B vaccine and may have decreased durability of post-vaccination immunity. Retrospective chart review was conducted for HIV-1 positive individuals aged ≥18 years who received hepatitis B vaccine at an urban HIV clinic. A total of 309 patients completed three doses and 178 had post-vaccine serology testing after the third dose. In multivariate analysis, time between the third dose and the first post-vaccine serology testing at 180–359 days (OR = 0.077, p = 0.049) and at ≥360 days (OR = 0.065, p = 0.019) were associated with poor vaccine responses. A significant decrease in seropositivity appeared as early as 180 days after the third vaccine dose, suggesting a rapid loss of vaccine-acquired hepatitis B surface antibody in HIV-infected persons. Our findings suggest that hepatitis B surface antibody should be tested at 6 to 12 months after completing primary vaccine series in order to detect early secondary vaccine failure.